Assessing Plantar Pressure Distribution and Time Parameters Following Total Ankle Replacement Surgery - Ryan Khan BA, MSc; Mansur Halai BSc (Hons), MBChB, MRCA, MRCS, FRCS; Timothy R. Daniels MD, FRCSC; Shahin Kayum MD; Ellie Pinsker PhD (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Other Introduction/Purpose: This study intended to use plantar pressure analysis to obtain supplementary objective outcome assessments of total ankle replacement surgery. Methods: Twenty subjects that were previously consented and booked for total ankle replacements participated in the study. Each subject performed a 10 meter walk prior to surgery and then again at six and twelve months post-operative. Plantar pressures were measured using the Pedar ® (by Novel, Munich, DE) pressure insoles. Six parameters: initial contact time, terminal contact time, maximum force time, peak pressure time, maximum force and peak pressure were calculated and averaged over trials in ten regions of foot. The parameters in each region were compared between pre and post-surgery. Results: We observed that patient’s hind foot total contact time notably increased after total ankle replacement. The average baseline hind foot contact time was 387ms, which increased to 448ms at 6 months post op and further increased to 487ms at the one-year visit. Suggesting that patients are able to better tolerate a load on the hind foot for considerably longer after having ankle replacement surgery. Conclusion: Plantar pressure measurements using the Pedar ® measurement system of pressure and time showed to be strong tools for objective evaluation of ankle joint replacement surgery. Future research comparing outcomes of ankle arthrodesis is planned Pedar software